Needs assessment of the University of the Philippines Diliman librarians on the UP University Library's radio program - LibRadio - Surio, Leo Michael G. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
Still airing today, LibRadio has been considered an established public service radio program of the of the University Diliman (UPD) University Library. Majority of the topics discussed in Libradio episodes were under the field of Library and Information Science (LIS) which could be of great benefit to librarians and information professionals rather than an ordinary listener.